2017
DOI: 10.1016/j.jvs.2016.07.130
|View full text |Cite
|
Sign up to set email alerts
|

Iliofemoral endarterectomy associated with systematic iliac stent grafting for the treatment of severe iliofemoral occlusive disease

Abstract: Combined iliofemoral endarterectomy and covered stenting of the EIA for treatment of severe occlusive lesions provided acceptable midterm results, probably because of the gain of diameter provided by covered stents. This technique avoids complications due to an aortic or iliac surgical approach and clamping as well as complications related to the presence of a prosthetic implant in an intra-abdominal position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
3
11
0
2
Order By: Relevance
“…Another possible option for focal lesions involving the EIA is to perform angioplasty alone using a drug-coated balloon, reserving stent implantation as a second option, in particular if a small stent would be needed. An adjunctive possibility described in the literature is iliofemoral endarterectomy associated with systematic iliac stent grafting as described by Maitrias et al, 23 in which the size of the stent is calibrated to the diameter of the endarterectomized distal EIA, allowing a gain in stent diameter, which is generally $8 mm in women with the use of this technique. This study has some limitations that are worth mentioning.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible option for focal lesions involving the EIA is to perform angioplasty alone using a drug-coated balloon, reserving stent implantation as a second option, in particular if a small stent would be needed. An adjunctive possibility described in the literature is iliofemoral endarterectomy associated with systematic iliac stent grafting as described by Maitrias et al, 23 in which the size of the stent is calibrated to the diameter of the endarterectomized distal EIA, allowing a gain in stent diameter, which is generally $8 mm in women with the use of this technique. This study has some limitations that are worth mentioning.…”
Section: Discussionmentioning
confidence: 99%
“…In study showed that a hematoma at the puncture site occurred in 15 (7.1%) of 212 groins, but none required surgical repair. 13 Our study shows that there no significant difference between Unilateral and kissing technique as regards sex and age. In a study showed that Baseline clinical characteristics (including age and sex) has not insignificant different between the both group.…”
Section: Discussionmentioning
confidence: 47%
“…9 In a study using kissing stent, Duplex imaging diagnosed significant restenosis in 15 (14.8%) of 101 patients and restenosis in 4 (4%), with recurrent symptoms in 17 (89.5%) of these 19 patients. 13 Our study shows that there no significant difference between Unilateral and kissing technique as regards access (Ipsilateral and contralateral femoral access & Left brachial access and contralateral femoral access). A study by Suh, Y et al reported that there no significant difference between single-stent and kissing technique as regards access(unilateral femoral, Bilateral femoral, Brachial artery).…”
Section: Discussionmentioning
confidence: 49%
“…Iliofemoral endarterectomy with proximal iliac stenting is a safe and effective alternative to traditional open surgery in patients with iliofemoral occlusive disease 5 . Studies have reported 5-year primary patency rate of 60% to 87%, primary assisted patency rate of 97%, and secondary patency rate of 98% for TASC C and D lesions treated with combined CFA endarterectomy and iliac stenting or stent grafting 1, 4. The described case provides a modified alternative to the traditional technique of retrograde iliac stenting, eliminating the need to clamp heavily calcified, diseased iliac vessels, thus allowing a more extensive proximal endarterectomy plane (Fig 4, A and B ) as well as a smoother transition and incorporation of the iliac stent grafts into the endarterectomized plane (Fig 4, C ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with aortoiliac and femoral occlusive disease, hybrid repair combining endovascular iliac stenting and femoral endarterectomy offers a less invasive alternative to aortobifemoral bypass, with shorter length of hospitalization and less resource use 1, 2, 3. It yields acceptable long-term results with higher primary patency rates with the use of covered stents compared with bare-metal stents 1, 4. Whereas this technique is ideal for stenotic iliac arteries, complete iliac occlusion extending into the proximal femoral arteries presents a more challenging scenario that can complicate the endarterectomy plane, proximal control, stent graft delivery, and apposition.…”
mentioning
confidence: 99%